Interventions for Ensuring Thermal Comfort Equality in Apartment Buildings - Dikmen, Nese; Elias-Ozkan, Soofia Tahira; Sumer Haydaraslan, Kubra (European Journal of Sustainable Development, 2017)
Energy reduction is one of the goals of sustainability. Thermal comfort and sustainability refers to smart dealing with natural resources to be acceptable for people. In order to provide thermal comfort to occupants, it is necessary to prevent excessive thermal transfers from the building’s envelope. To this end thermal insulation is provided and windows with low U values are installed in buildings. However, the orientation of living spaces in a building determines the amount of solar gains from the facades, which in turn influences the thermal conditions within. Thus, spaces facing different directions need different amount of thermal control to achieve thermal equality. On the other hand, the standard practice for reducing the energy loads of a building is to select the same type of thermal insulation and windows for the entire façade, regardless of the direction of the external walls. This state of affairs gives rise to an inequality in the thermal comfort conditions of residential units facing different orientations. The aim of this study was to eliminate this inequality through certain local interventions on the part of the residents themselves; e.g. increasing insulation, reducing U values of the windows and providing solar shading. To this end an apartment building was modelled with the aid of an energy simulation software: DesignBuilder. The heating and cooling loads obtained from the residential units facing North, South, East and West directions were compared for various intervention scenarios, based on the application of various thicknesses of insulation inside the external walls, improved U values for windows and solar shading devices; as well as natural ventilation. The simulated energy loads demonstrate the effectiveness of case based refurbishment interventions for achieving thermal equality and energy expenditures in all units regardless of their orientations. Keywords: Orientation, thermal insulation, U-value, heating load, cooling load